COVID-19 laboratory tests and their implication in dental treatment - Bote, Sebastiana Arroyo (2020)
Since the identification of the SARS-CoV-2 virus as the cause of the disease and the COVID-19 pandemic, the diagnosis of the infected population, the control of risk groups, and the immunity of the population have been the main objectives of the scientific community. Laboratory tests are essential to diagnose infected population, determine the status and evolution of the disease in patients with symptoms, and the immunity that each social group has developed. Depending on the results of the different COVID-19 laboratory tests, healthcare professionals indicate different actions and treatments. Dentists must take into account the results of COVID-19 laboratory tests of their patients as input before to the performance of any dental treatments, given the high risk of spread and contagion that dental treatments entail.